Flow dynamics behaviour of a novel liquid-liquid hydrocyclone with varying upper cylindrical lengths and number of inlets - Osei, H. (Asian Research Publishing Network, 2016)
The use of a liquid-liquid hydrocyclone in the downhole is one the few environmentally friendly ways by which water production can be limited, while at the same time ensure maximum recovery. The understanding of the fluid flow behaviours that bring about better separation and performance is therefore important and should not be underestimated. This work, through numerical simulation, studied the effects that the tangential inlet(s) and the height of the upper cylindrical section of a liquid-liquid hydrocyclone have on its hydrodynamics. The results showed that the single inlet hydrocyclones unlike the twin inlet types are more prone to producing asymmetrical reversal flow which meanders along the axis of the hydrocyclone. This can affect the efficiency of separation if the particles are not well segregated. The single inlet 30 mm upper cylindrical length (UCL) hydrocyclone produced the highest velocity fields that could ensure better fluid swirling and rotation, and the greatest upward core flowing pressure that could ensure better transportation of the lighter fraction concentrated at the core. Therefore, the single inlet hydrocyclone with 30 mm UCL is the best among the studied cyclonic separator types and its use for downhole oil/water separation can enhance the problem of excessive water production. Â©2006-2016 Asian Research Publishing Network (ARPN).